Analisis Pengaruh Return On Equity, Earning Per share, dan Debt To Equity Ratio Pada Harga Saham JII-70 Selama Pandemi Covid-19 - Susanti, Nopi; Canggih, Clarashinta (Jurnal Ekonomika dan Bisnis Islam, 2022)
The purpose of this study is to look at the factors that affect stock prices, such as ROE, EPS, and DER during the Covid-19 pandemic. All issuers on the IDX listed in JII 70 are the population in this study. The sampling technique used purposive sampling, in order to obtain a sample of 48 stocks. The data in this study used panel data obtained from the IDX website. Descriptive statistical analysis and panel data regression are data analysis techniques used in this study. The results of the study indicate that ROE, EPS and DER have a significant effect on the stock price of JII-70 companies during the Covid-19 pandemic. While partially ROE, EPS does not have a significant, only DER has a significant effect on share prices of companies that are members of JII 70 during the Covid-19 pandemic.